GB virus C Viremia and Anti-E2 Antibody Response Among Hemodialysis Patients in Gorgan, Iran - Kelishadi, Mishar (Jundishapur J Microbiol, 2014)
BACKGROUND: GB Virus C is a blood-borne virus and a member of Flaviviridae, like hepatitis C that is distributed globally and puts hemodialysis patients at high risk of developing liver disease. The clinical significance of GBV-C in this population remains unclear. OBJECTIVES: The current study aimed to evaluate GBV-C infection among hemodialysis patients. PATIENTS AND METHODS: Totally, 149 patients receiving hemodialysis were included in the study. The detection of GBV-C sequences in plasma was done by the nested Reverse transcription polymerase chain reaction (RT-PCR) using specific primers selected from highly conserved regions of 5' UTR of GBV-C and antibodies to the envelope protein of GBV-C (anti-E2 GBV-C antibody) were analyzed by also serological methods. In addition, Hepatitis B surface antigen (HBsAg), Hepatitis B core antibody (HBcAb) IgM, anti- Hepatitis C virus (HCV) and anti- hepatitis E virus (HEV) Ab was determined in patients who were GBV-C RNA and anti-E2 GBV-C antibody positive. RESULTS: The total prevalence of GBV-C infection was 14.7% (95%CI: 0.09-0.21) among patients receiving hemodialysis. The rate of GBV-C viremia and anti-E2 antibody positivity were 6.04% and 10.73%, respectively. Among the subjects who were positive for GBV-C, 27.27% (95% CI: 0.02-0.09), 45.45% (95% CI: 0.03-0.11), 59.9% (95% CI: 0.06-0.16) and 0% (95% CI: 0.01-0.07) were positive for anti-HCV, anti-HBsAg, anti-HBc IgM and anti-(HEV) Ab, respectively. In addition, the rate of both anti-HBc IgM /anti-HCV/ HBsAg and anti-HBc IgM /anti-HCV positivity in GBV-C infected cases were 9.09%. The liver enzymes were normal in all of them. There was significant difference between GBV-C exposures with viral hepatitis co-infection, but there was no correlation between GBV-C exposure with gender, age, ethnicity, time on dialysis and history of blood transfusions. A relatively high frequency of positivity GBV-C-exposure among hemodialysis patients suggested that the transmission route for GBV-C may be nosocomial transmission, and via transfusions. CONCLUSIONS: The current study found a relatively high frequency of positivity GBV-C-exposure among the patients receiving hemodialysis in the area understudy. Nosocomial transmission seems to be the main route of GBV-C infection in the area.